Patau syndrome [partial trisomy]: A case study - RUDRAGOUDA S BULAGOUDA,; B.M BANNUR,; KEERTI K,; BHEEMSHETTY S. PATIL,; GURUSHANTAPPA S KADAKOL, (International Journal of Pharma and Bio Sciences, 2017)
We report a two newborn Childs with clinical symptoms of Patau syndrome, Karytotyping technique was used to determine chromosomal abnormalities and confirmed diagnosis. Patau syndrome is a rare and severe form of autosomal trisomics. It is coused by a chromosomal abnormality, in which some or all of the cells of the body contain extra genetic material from chromosome 13 disrupts the normal course of development, causing multiple and complex organ defects. It is related with more loss of pregnancy and survival of infants is very poor. Neonates with trisomy 13 die usually within the few hours or days of life. Eighty percent of babies affected this syndrome die within first month of life.The incidence rate of Patau Syndrome is1 in 20,000 live births. Survivors have profound mental retardation and other multiple physical abnormalities like cardio vascular defects, brain or spinal cord abnormalities,cleft palate or lip, extra fingers or toes and decreased muscle tone.